2021
DOI: 10.1101/2021.10.17.463805
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of oxytocin in modulating self-other distinction in human brain: a pharmacological fMRI study

Abstract: The self-other distinction is crucial in human social cognition and social interaction. Studies have found that oxytocin (OT) sharpens the self-other perceptual boundary but with mixed results. Further, little is known if the effect of OT on self-resemblance face perception exists, especially on its neural basis. Moreover, it is unclear if OT would influence the judgment in self-other discrimination when the other is a child or an adult. In the current double-blinded, placebo-controlled study, we investigated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…A single dose of 24 IU of oxytocin or placebo was administered intranasally. More details regarding drug administration have been described in one of our published studies (Wang et al, 2022;Wu, Feng, et al, 2020).…”
Section: Resting and Task Data Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single dose of 24 IU of oxytocin or placebo was administered intranasally. More details regarding drug administration have been described in one of our published studies (Wang et al, 2022;Wu, Feng, et al, 2020).…”
Section: Resting and Task Data Setsmentioning
confidence: 99%
“…For the resting dataset, we used fMRI data similar to the resting-state data that have been published for resting-state network studies only (Wu, Liu, et al, 2020;Zheng et al, 2022;Zheng et al, 2021). For the task dataset, we used the task fMRI data that were used for task fMRI analyses only (Wang et al, 2022), which provided the task descriptions. Specifically, we used a face perception task with morphed self and other faces (Wang et al, 2022).…”
Section: Resting and Task Data Setsmentioning
confidence: 99%
“…These results indicated that OT did not influence behavioral performance in the face perception task. Further details are provided in one of our published studies (Wang et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…A single dose of 24 IU of oxytocin or placebo was administered intranasally. More details regarding drug administration have been described in one of our published studies (Wang et al, 2022; Wu, Feng, et al, 2020). The participants then underwent a resting-state scan (300s) before the task-state scan (240s).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation